Analysis of Link Popularity among the Nepal Governments’ Websites by using HITS Algorithm - Bhandari,, Bhim; Ram Joshi, Dr. Shashidhar (IJRDO -Journal of Computer Science Engineering, 2017)
New innovations in science and technology, communication becomes faster and easier. Informationdissemination tools become the URLs through internet. Nepal Government has taken major initiatives and hasgood impact for g-governance. In this context, a close study among the governmental organizations’ URLs andtheir links from one web page to another helps for information dissemination. A web page's link popularity ismeasured by the number of other web pages that link to it, and links from pages on other web sites. The pagepopularity is measured by using HITS and PageRank methods. The two main factors relevance and reputationare considered as major findings during study. Relevance is a measure of how easy it is for the search engineto tell that your web page is really about the search term that's been used. It improves relevance with on-pagesearch engine optimization, and talks about that extensively on other pages of our site. Reputation is measuredby the number of links coming into one web site and the quality of those links. The most common term for that is"link popularity".Keyword formulation and link definition in the government web sites is random thus status of link popularity isweak. Out of twenty-nine web sites on five websites have implemented the concept of the inlink and outlink i.e.relevancy is better